2011
DOI: 10.1186/1471-2458-11-101
|View full text |Cite
|
Sign up to set email alerts
|

Which chronic diseases and disease combinations are specific to multimorbidity in the elderly? Results of a claims data based cross-sectional study in Germany

Abstract: BackgroundGrowing interest in multimorbidity is observable in industrialized countries. For Germany, the increasing attention still goes still hand in hand with a small number of studies on multimorbidity. The authors report the first results of a cross-sectional study on a large sample of policy holders (n = 123,224) of a statutory health insurance company operating nationwide. This is the first comprehensive study addressing multimorbidity on the basis of German claims data. The main research question was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
238
6
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(283 citation statements)
references
References 25 publications
17
238
6
22
Order By: Relevance
“…It will help in taking into consideration different patterns of multimorbidity including triplets and higher order combinations of chronic conditions in studying HRQoL. Studies have shown that the co-occurrence of three or more chronic conditions in older adults is common [15,16] but there are no current studies exploring the effects, for example, of most prevalent triplets or higher order combinations of chronic conditions on HRQoL. Studies that consider the effects the crude number of chronic conditions co-occurring in an individual have on HRQoL show that the effects of multimorbidity as triplets or higher order combinations may be much more substantial than the one implied by multimorbidity as pairs [11].…”
Section: Short Communicationmentioning
confidence: 99%
“…It will help in taking into consideration different patterns of multimorbidity including triplets and higher order combinations of chronic conditions in studying HRQoL. Studies have shown that the co-occurrence of three or more chronic conditions in older adults is common [15,16] but there are no current studies exploring the effects, for example, of most prevalent triplets or higher order combinations of chronic conditions on HRQoL. Studies that consider the effects the crude number of chronic conditions co-occurring in an individual have on HRQoL show that the effects of multimorbidity as triplets or higher order combinations may be much more substantial than the one implied by multimorbidity as pairs [11].…”
Section: Short Communicationmentioning
confidence: 99%
“…27 In addition, several methodological issues relating to studies on multimorbidity are still unresolved. 1,28 These include what the best way to measure it would be, 29 which clusters of diseases are more harmful 30 and what role sex has in relation to development of multimorbidity. 31 The aims of the present study were to determine the prevalence of multimorbidity in a population of adult Brazilians and to investigate the relationship between its occurrence and socioeconomic position, measured via educational attainment.…”
mentioning
confidence: 99%
“…The prevalence of clinical knee osteoarthritis (OA) increases steadily with age, so that almost half of the population aged 80 and over is affected [2]. OA is associated with pain, functional disability and impaired quality of life [3] and is one of the most disabling diseases in the aged [4,5].…”
Section: Introductionmentioning
confidence: 99%